Sinthesis, characterizacion and properties of the 7,m nylons - Pérez Rodríguez, íngel Tomás; Pérez Pérez, Marian; Fernández Santín, José María (Rev. Téc. Fac. Ing. Univ. Zulia, 2016)
This work is a part of the investigations associated to the study of odd-odd polyamides (n,m) obtained by means of the interfacial policondensation with agitation starting from diamines and commercial dichloro acids. In this article the results obtained for the 7,m nylons (m=5; 7; 9) are shown. The investigation has been developed in the characterization and synthesis areas, centering the objective on the analysis of the properties of these polymers for their foreseeable implementation in the electronic sector due to the active electric properties they possess. As results, the following ones stand out: the nylons 7,m are procesable by fusion, they possess high thermal stability and can be obtained with high cristalinity by slow cooling of the melt. The films of the 7.7 and 7.9 nylons are operable and possess acceptable mechanical characteristics, absorbing up to 1,3% of water when exposed to an environment regulated to 23 ÂºC and 55% of relative humidity.